THE RELATION OF SMOKING AND ALCOHOL CONSUMPTION WITH CORONARY HEART DISEASE AND ITS RISK FACTORS (ESSE-RF IN KEMEROVSKAYA REGION) - S. A. Maximov; D. P. Tsygankova; G. V. Artamonova (Кардиоваскулярная терапия и профилактика, 2018)
Aim. Analysis of the relation of smoking and alcohol consumption with coronary heart disease (CHD) and its main risk factors (RF).Material and methods. The data analyzed, from the multicenter epidemiological study ESSE-RF (Epidemiology of Cardiovascular Diseases and Risk Factors in Russia) in Kemerovaskaya region, on the random sample of male and female inhabitants of 25-64 y.o. (n=1628). With the interview method, data gathered on alcohol consumption and smoking status of the participants, as on their social level, anamnesis, presence of angina pectoris. During medical investigation the values of lipid profile were obtained, weight and height, blood pressure and electrocardiography. The assessment of relation of smoking and alcohol with CHD and its RF was done with the logistic regression.Results. After correction for the modifying RF, most adverse associations were found in the heaviest drinkers regardless smoking: high significant risks of triglyceridemia — odds ratio (OR) is 2,46-4,59, and CHD — OR 3,023,89, as the tendency for statistical significance of hypercholestrolemia. In smokers and heavy alcohol consumers there is tendency to hypertension and diabetes risk. In smokers nonand moderate drinkers there are tendencies for higher hypertension risk, as of higher triglycerides and CHD risk. The category smokers/non-drinkers is characterized by the highest among others significant risk of CHD (OR 9,05). Among all studied groups, the best position hold non-smokers/moderate drinkers, who present with the risks of CHD and RF similar to reference, or lower (non-significant).Conclusion. Results of the study witness on the relation of CHD and its RF with the combination of smoking and alcohol consumption.